2021
DOI: 10.3389/fpsyg.2021.710122
|View full text |Cite
|
Sign up to set email alerts
|

New Technologies' Commercialization: The Roles of the Leader's Emotion and Incubation Support

Abstract: New technologies, such as brain-computer interfaces technology, advanced artificial intelligence, cloud computing, and virtual reality technology, have a strong influence on our daily activities. The application and commercialization of these technologies are prevailing globally, such as distance education, health monitoring, smart home devices, and robots. However, we still know little about the roles of individual emotion and the external environment on the commercialization of these new technologies. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
0
6
0
1
Order By: Relevance
“…TCC is the ability of enterprises to timely transform technology or ideas into products or services that match the users' needs (Shan et al, 2021;Zahra & Nielsen, 2002). Technology commercialization plays a very important role for enterprises, especially for high-tech enterprises, which have high innovation and high growth (Dai et al, 2018).…”
Section: Technology Commercialization Capabilitymentioning
confidence: 99%
“…TCC is the ability of enterprises to timely transform technology or ideas into products or services that match the users' needs (Shan et al, 2021;Zahra & Nielsen, 2002). Technology commercialization plays a very important role for enterprises, especially for high-tech enterprises, which have high innovation and high growth (Dai et al, 2018).…”
Section: Technology Commercialization Capabilitymentioning
confidence: 99%
“…Past research has shown that entrepreneurs experience more extreme emotions in the innovation process and that using appropriate emotion regulation strategies to deal with these extreme fluctuating emotions can facilitate innovation adoption and implementation ( Huy, 2005 ; Raffaelli et al, 2019 ; Shan et al, 2021 ). More specially, innovation involves mobilizing sufficient resources and challenges members’ basic assumptions about the organization, which define intersubjective reality and provide a way of dealing with ambiguous, uncontrollable events ( Schein, 1992 ; Yu et al, 2020 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Traditionally, therapies aimed at remediating facial affect recognition deficits used pictures showing a range of emotions. However, facial movements, voice, and gestures are important cues for the recognition (Roark et al, 2003 ; Garrido et al, 2016 ; Pan et al, 2021 ; Tiwari et al, 2021 ) and regulation (Colombo et al, 2019 ; Shan et al, 2021 ; Wang et al, 2022 ) of affect. Therefore, virtual humans (VHs) overcome many restrictions on the use of static images through animation, or even videos, by offering an unlimited set of designs (avatars in the social context) to practitioners (Fernández-Caballero et al, 2017 ; García et al, 2018 ; del Aguila et al, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%